Inventing Africa History, Archaeology and Ideas - Derricourt, Robin (Pluto Press, 2011)
Inventing Africa is a critical account of narratives which have selectively interpreted and misinterpreted the continent's deep past.Writers have created alluring images of lost cities, vast prehistoric migrations and golden ages of past civilisations. Debates continue on the African origins of humankind, the contributions of ancient Egypt to the world and Africa's importance to global history.Images of 'Africa', simplifying a complex and diverse continent, have existed from ancient Mediterranean worlds, slave trading nations and colonial powers to today's political elites, ecotourists and aid-givers. Robin Derricourt draws on his background as publisher and practitioner in archaeology and history to explore the limits and the dangers of simplifications, arguing - as with Said's concept of 'Orientalism' - that ambitious ideas can delude or oppress as well as inform.Defending Africa against some of the grand narratives that have been imposed upon its peoples, Inventing Africa will spark new debates in the history of Africa and of archaeology.